2007
DOI: 10.1159/000112646
|View full text |Cite
|
Sign up to set email alerts
|

The c.1-260C>T Promoter Variant of CD14 but Not the c.896A>G (p.D299G) Variant of Toll-Like Receptor 4 (TLR4) Genes Is Associated with Inflammatory Bowel Disease

Abstract: Background: Inflammatory bowel disease (IBD) results from an aberrant immune response to the indigenous intestinal flora in genetically susceptible hosts. Therefore, the study of candidate genes involved in host pathogen interactions is of key interest. Methods: In this two-center, retrospective German and Hungarian cohort study, patients with Crohn’s disease (CD) (n = 379; German n = 235, Hungarian n = 144) and ulcerative colitis (UC) (n = 263; German n = 145, Hungarian n = 118) and healthy controls (n = 605;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 76 publications
1
26
1
Order By: Relevance
“…In a retrospective German and Hungarian cohort study, patients with CD and UC were genotyped for the presence of the CD14 c.1-260C>T promoter variant and the TLR4 D299G variant. In this study, in German and Hungarian populations, IBD appears to be associated with the CD14 c.1-260C>T promoter variant, but not with the TLR4 D299G variant [45] . Recent data suggest that neither of these 2 variants is causal, but they may be in linkage disequilibrium with, as yet unidentified, causal variants [46][47][48] .…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In a retrospective German and Hungarian cohort study, patients with CD and UC were genotyped for the presence of the CD14 c.1-260C>T promoter variant and the TLR4 D299G variant. In this study, in German and Hungarian populations, IBD appears to be associated with the CD14 c.1-260C>T promoter variant, but not with the TLR4 D299G variant [45] . Recent data suggest that neither of these 2 variants is causal, but they may be in linkage disequilibrium with, as yet unidentified, causal variants [46][47][48] .…”
Section: Discussionmentioning
confidence: 44%
“…In our study, we found no difference in the prevalence of these mutations in our CD and UC patients, and controls. Recently, other studies have failed to find the association of the D299G and T399I SNPs of TLR4 gene [24,[42][43][44][45] . In a retrospective German and Hungarian cohort study, patients with CD and UC were genotyped for the presence of the CD14 c.1-260C>T promoter variant and the TLR4 D299G variant.…”
Section: Discussionmentioning
confidence: 99%
“…In a German cohort, the CD14 promoter 1-260C>T singlenucleotide polymorphism (SNP) was associated with UC, but not CD, while the opposite was found in a Hungarian cohort. No association with IBD of the TLR4 896A>G SNP was found in either cohort [14] . In a Belgian study, the allele frequency of the TLR4 A299G polymorphism, affecting the extracellular domain of TLR4 that is associated with an abrogated response, was significantly higher in CD (11% vs 5%, P = 0.004 in one cohort and 12% vs 5%, P = 0.007 in another cohort) and in UC patients (10% vs 5%, P = 0.027) compared with controls [22] .…”
Section: Tlr4mentioning
confidence: 68%
“…They are transmembrane receptors that are found either on the cell membrane (TLR1, 2, 4, 5 and 9) or on intracellular organelles (TLR3, 7 and 8) [10,11] . TLRs are expressed throughout the gastrointestinal (GI) tract on intestinal epithelial cells (IECs), myofibroblasts, enteroendocrine cells, and on immune cells within the lamina propria, such as T cells, and dendritic cells (DCs) [12][13][14][15][16] . Extracellular domains of TLRs consist of leucine-rich repeats (LRRs), whereas their intracellular component contains a TIR (Toll/IL-1 receptor) domain, exhibiting homology with the interleukin-1 receptor (IL-1R) superfamily.…”
Section: Tlrsmentioning
confidence: 99%
“…Epidemiological studies show an association between TLR4 polymorphism and susceptibility to IBD. In a Belgian study, the allele frequency of the TLR4 A299G polymorphism was significantly higher in CD and in UC patients compared with controls, whereas no association with IBD of the TLR4 polymorphim was found in Hungarian and German cohort (24,25). The study about polymorphisms of TLR1, 2 or 6 in the pathogenesis of IBD are scarce.…”
Section: Discussionmentioning
confidence: 97%